The Box-Behnken Response Surface Methodology Approach to Optimize Tensile Strength Load in Resistance Spot Welding Using SPCC-SD Steel - Mulyadi, Dodi; Amir, Amir; Cepi Budiansyah, Ade; Sukarman, Sukarman; Khoirudin, Khoirudin; Arif Wibowo, Ludvi; Kumbarasari, Shanti (Jurnal Teknik Mesin Mechanical Xplore, 2024)
This article describes an experimental investigation into optimizing spot welding resistance (RSW) using a spot-welding machine equipped with a dual-electrode Pressure Force System (PFS). The optimization procedure entails the incorporation of SPCC-SD (JIS G 3141), a low-carbon steel that finds extensive application in the automotive sector. With the widespread use of SPCC-SD steel, RSW is an essential process in the automotive industry for assembling body components. This study employs the Box-Behnken Response Surface Methodology (Box-Behnken-RSM) to optimize the tensile strength load (TS-load), a critical parameter in RSW, through a meticulous analysis of the interplay between Holding Time, Squeezing Time, Welding Current, and Welding Time. Through the methodical design of experiments, the collection of Tensile Strength Load data, and the application of statistical modeling via RSM, this study employs SPCC-SD steel to determine the optimal values for these variables in RSW. The results above readily offer a valuable understanding of the most significant determinants and their interrelationships, thus facilitating advancements in welding methodologies and quality control in the automotive manufacturing sector. This study employs the Box-Behnken Response Surface Methodology to investigate the impacts and interrelationships of different parameters thoroughly. It aims to enhance the TS-load using SPCC-SD steel during the resistance spot welding procedure. This research contributes to advancing welding methodologies employed in the automotive manufacturing sector.